HEPATECTOMY FOR PYOGENIC LIVER ABSCESS TREATMENT: EXCEPTION APPROACH? - PAIS-COSTA, Sergio Renato (Arq Bras Cir Dig, 2018)
BACKGROUND: Percutaneous drainage for pyogenic liver abscess has been considered the gold-standard approach for the treatment on almost of the cases. However, when percutaneous drainage fails or even in some especial situations, as multiloculate abscess, lobe or segment surgical resection can solve infectious clinical condition. AIM: To report a series of patients who underwent hepatectomy for pyogenic liver abscess performed by a single surgical team. METHODS: Eleven patients were operated with ages ranging from 45-73 years (mean and median 66 years). There were eight men and three women. The etiologies were: idiopathic (n=4), biliary (n=2), radiofrequency (n=2), direct extension (n=1), portal (n=1), and arterial (n=1). The mean lesion diameter was 9.27 cm (6-20 cm). RESULTS: The mean operation length was 180 min (120-300). The mean intra-operative blood loss was 448 ml (50-1500). Surgical approaches were: right hepatectomy (n=4), left hepatectomy (n=3), left lateral sectioniectomy (n=1), right posterior sectioniectomy (n=2), resection of S8 (n=1), and S1 (n=1). Postoperative morbidity rate was 30%, while mortality was null. Median hospital stay was 18 days (5-45). The median follow-up period was 49 months (13-78). There was single lesion recurrence. CONCLUSION: Hepatectomy can be done as exception approach for pyogenic hepatic abscess treatment; it is a good therapeutic option in special situations.